Pengembangan Sistem Informasi Manajemen Bimbingan Belajar (Studi Kasus: Naoyuki Academic Center) - Widya Saptiani; Achmad Arwan; Agi Putra Kharisma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Naoyuki Academic Center Japanese tutoring center has 3 divisions in managing its business. In the marketing division, business marketing information is routinely made by marketing once a month about the target market, potential market and market levers are still done manually that is using paper. In the human resources division, the curriculum vitae information of employees and teachers still uses paper so that if it is damaged or lost, the recruitment staff will have difficulty finding this information. In addition, in the financial division, the process of recording financial cash flow data, student payment data, and employee and teacher payrolls made by accountants is still done manually making it difficult to recap financial data because the files are kept separately and the director has difficulty in evaluating financial institution. The Naoyuki Academic Center's tutoring institution management information system was built to answer the problems that exist in the institution. The process of recording information for marketing divisions, human resources divisions, and financial divisions can be accessed at any time because web-based and centrally stored data can assist each division in finding the information needed. The tutoring management information system was built with Waterfall Model, and the MVC concept (model, view, controller) in the Laravel framework. Tests carried out namely using white-box testing with unit testing, validation testing and black-box testing with compatibility testing. The results of the tests obtained from unit tests and validation tests are 100% valid, and compatibility test results show the system can be used well in different browser scopes.